Grazing exclusion increases soil CO2 emission during the growing season in alpine meadows on the Tibetan Plateau. (February 2018) - Guo, Na; Wang, Aidong; Allan Degen, A.; Deng, Bin; Shang, Zhanhuan; Ding, Luming; Long, Ruijun
Abstract: Soil CO2 emission is a key part of the terrestrial carbon cycle. Grazing exclusion by fencing is often considered a beneficial grassland management option to restore degraded grassland, but its effect on soil CO2 emission on the northeastern Tibetan Plateau is equivocal and is the subject of this study. Using a closed static chamber, we measured diurnal soil CO2 flux weekly from July, 2008, to April, 2009, in response to grazing and grazing exclusion in the alpine meadow and alpine shrub meadow. Concomitantly, soil temperature was measured at depths of 5 cm, 10 cm, 15 cm and 20 cm with digital temperature sensors. It emerged that: 1) non-grazed grasslands emitted more soil CO2 than grazed grasslands over the growing season; 2) the alpine shrub meadow emitted more soil CO2 than the alpine meadow; the annual cumulative soil CO2 emissions of alpine meadow and alpine shrub meadow were 241.5–326.5 g C/m 2 and 429.0–512.5 g C/m 2, respectively; 3) seasonal patterns were evident with more soil CO2 flux in the growing than in the non-growing season; and 4) the diurnal soil CO2 flux exhibited a single peak across all sampling sites. In addition, soil CO2 flux was correlated positively with soil temperature at 5 cm, but not at the other depths. We concluded that grazing exclusion enhanced soil CO2 emission over the growing season, and decreased carbon sequestration of alpine meadow and alpine shrub meadow on the northeastern Tibetan Plateau. Since an increase in soil temperature increased soil CO2 flux, global warming could have an effect on soil CO2 emission in the future. Highlights: Non-grazed grasslands emitted more soil CO2 than grazed grasslands over the growing season. Seasonal patterns were evident with more soil CO2 flux in the growing than in the non-growing season. The diurnal soil CO2 flux exhibited a single peak across all sampling sites. Soil CO2 flux was correlated positively with soil temperature at 5 cm. Grazing exclusion enhanced soil CO2 emission over the growing season on the Tibetan Plateau.